DIVINE SOVEREIGNTY, INDIAN PROPERTY LAW, AND THE DISPUTE OVER THE PADMANABHASWAMI TEMPLE - Deepa Das Acevedo
Secular governance in India was meant to have incorporated religion within public life, but